PENUNTUTAN PERAMPASAN HARTA BENDA TERDAKWA KORUPSI YANG DIDUGA BERASAL DARI HASIL KORUPSI - Nazamuddin Nazamuddin; Muhammad Nur; Yulia Yulia (Program Studi Magister Hukum Universitas Malikussaleh, 2022)
This study discusses the handling of corruption crimes that have been handled by the Central Aceh District Attorney with the formula for the problem: (1) how is the arrangement for prosecuting the confiscation of the property of the accused perpetrators of corruption which allegedly originates from the proceeds of criminal acts of corruption based on Law Number 20 of 2001 Regarding the Eradication of Criminal Acts of Corruption, and (2) what is the legal procedure for confiscation of assets of perpetrators of corruption as determined by the Prosecutor's Office. This type of research is normative-empirical law research (applied law research), the data source is a direct source (primary data) or data obtained from indirect sources (secondary data). The method of collecting data is through document or literature research techniques (library research) and field research techniques (field research). Based on the results of the study, the authors conclude: (1) The mechanism for prosecuting the confiscation of the defendant's property from a criminal act of corruption is carried out by two mechanisms, namely criminal instruments (criminal charges) and civil instruments (civil lawsuits). (2) The process carried out by the Prosecutor in prosecuting the confiscation of the assets of the defendant in a criminal act of corruption is regulated through the Regulation of the Prosecutor's Office of the Republic of Indonesia Number 7 of 2020. (3) The obstacles faced by the prosecutor in prosecuting the confiscation of the defendant's property resulting from a criminal act of corruption consist of assets resulting from the act of corruption. corruption crimes are obscured or transferred to other parties, corruption assets are exhausted, assets are pledged to other parties, the perpetrators of corruption crimes have died, assets resulting from corruption crimes have been transported abroad.